2016
DOI: 10.28930/jitkt.v7i2.11254
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy Improvement on Sea Surface Height Estimation Based on Waveform Retracking Analyses of Jason-2 Satellite in Java Sea

Abstract: <p><em>A waveform created by the reflected signal from altimeter satellite in offshore is generally in ideal shape (Brown-waveform) and produces an accurate sea surface height (SSH) estimation. However, over coastal waters, the waveform shape becomes complex due to a disruption by reflected signal from land, resulting inaccurate SSH estimation. The objective of this research was to improve the accuracy of SSH estimation employing waveform retracking analyses of Jason-2 altimeter satellite data in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…However, the algorithm that most often presented the highest IMP was the Threshold 10%. The finding in the Java Sea also showed that Threshold 10 was one of the best retrackers [23,25]. Conversely, in Natuna Sea, which was shallow water, Threshold 10 gave poor performance [29].…”
Section: Evaluation Of Waveform Retracking Performance Against Geoid Heightmentioning
confidence: 80%
See 3 more Smart Citations
“…However, the algorithm that most often presented the highest IMP was the Threshold 10%. The finding in the Java Sea also showed that Threshold 10 was one of the best retrackers [23,25]. Conversely, in Natuna Sea, which was shallow water, Threshold 10 gave poor performance [29].…”
Section: Evaluation Of Waveform Retracking Performance Against Geoid Heightmentioning
confidence: 80%
“…Over the Indonesian seas, previous studies (e.g., [23,25,28,29]) reported the performance of several retrackers using the geoidal height data, which highlighting the precision of retracked SSHs. While the accuracy of the retrackers is also valuable, such studies are yet to be done, thus becoming the motivation of this study.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations